Reconstruction Concept of Restorative Justice in the Crime of Theft with Elderly Perpetrators in Batam - Alhakim, Abdurrakhman; Hutauruk, Rufinus Hotmaulana; Azlyn, Nurul (Jurnal Independent, 2023)
AbstractRestorative justice is an alternative to solving criminal cases in which the criminal justice procedure mechanism focuses on punishment which is changed into a dialogue and mediation process involving the perpetrator, victim, family of the perpetrator/victim, and other related parties. Indeed, the issue of sanctions is a very important issue in the implementation of the content of criminal law because it is a reflection of norms and rules that contain the values of a society. In its implementation, the determination and provision of criminal sanctions based on the law prioritizes Primum Remedium rather than Ultimum Remedium. The purpose of this research is to review, analyze and reconstruct the concept of restorative justice as an alternative to the settlement of criminal acts, especially against elderly perpetrators of theft in Batam city. Based on the result of the research, there is still no special regulation related to the settlement of theft crime by the elderly in Batam City, there is still a need for the establishment of legal institutions/agencies that develop the concept of restorative justice and the lack of knowledge of the people of Batam City on the concept of restorative justice